Cohabitation in shared landscapes in Arctic Yakutia: social relations between reindeer herders/hunters and wolves - Jefanovas, Aivaras (Institutional Repository of Vilnius University, 2021)
This ethnographic study is devoted to the reindeer herders and hunters of Arctic Yakutia who live in the mountainous taiga and tundra landscapes and engage in social relationships with other than humans beings, specifically wolves. This dissertation explores how these interspecific relationships, which are based on aggressive interaction and peaceful existence, intermingle and account for the complexity of the cohabitation of humans and predators in the shared landscapes. Furthermore, this thesis aims to demonstrate how human-predator cohabitation in Arctic Yakutia can be shaped by reciprocal interaction and interspecific communication through signs. To give a deeper understanding of contemporary interactions of wolves and the reindeer herders/hunters of Arctic Yakutia, this study also explores the animistic worldview of the herders/hunters and examines the interspecific relations from historical, socio-economic, political and spatial viewpoints.